POLICY FOR BUILDING A CONDUCIVE ORGANIZATIONAL CLIMATE AT AL-HIKMAH ISLAMIC MIDDLE SCHOOL MAYONG JEPARA - Utomo, Budi; Muharom, Fauzi; Setiyatna, Hery (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This research aims to find out Policy for Building a Conducive Organizational Climate at Al-Hikmah Islamic Middle School, Mayong, Jepara. The method used in this research is a descriptive qualitative research method field research. The results of the research that has been conducted are as follows: one form of policy that must be used by the principal in building a conducive organizational climate is: 1) Mutual respect, 2) Mutual respect, 3) Mutual support, 4) Trying to put yourself in the position of the other party, 5) Taking mutually beneficial actions. Al-Hikmah Islamic Middle School, Mayong, Jepara has a way of implementing policies to build a conducive organizational climate at Al-Hikmah Islamic Middle School, Mayong, Jepara as follows: 1) Clear organizational structure, 2) Analysis of teacher and employee performance standards. 3) Responsibility, 4) Recognition, 5) Support, 6) Goals, 7) Commitment, 8) Student Skills. Understanding school climate as aintangiblebut it is important for an organization and is analogous to the personality of an individual.